Integrasi Upaya Kesehatan Bersumberdaya Masyarakat (UKBM) Sebagai Rintisan Posyandu Prima di Wilayah Kerja Puskesmas Kartasura - Yuyun Setyorini; Ratna Wirawati Rosyida; Koko Wahyu Tarnoto; Sri Widyastari; Yopi Harwinanda Ardesa (Jurnal Empathy Pengabdian Kepada Masyarakat, 2024)
Background: Integration of primary health services, which is part of primary health service transformation activities by forming Posyandu Prima. Posyandu prima is a forum for community empowerment that provides health services according to needs in an integrated manner in the village. Methods: Community service with the title Integration of UKBM as a pioneer of prima posyandu in Pabelan Village, Kartasura District, Sukoharjo Regency, in March - September 2023. The stages carried out were preparation, implementation, evaluation, and reporting. Results: The implementation of UKBM integration went well by involving elements of the community (health workers, health cadres, community leaders, and cadets). Most respondents were female (67.2%; n = 41), and their high school education level was 59% (n = 36). Knowledge and practice after the implementation of activities are good (98.4%, n = 60). Conclusion: Increasing the knowledge and skills of adolescent health cadres in efforts to promote and prevent the risk of non-communicable diseases through efforts to detect simple diseases early, as well as the implementation of adolescent posyandu activities in the community in adolescent groups.